CONVEYOR BELT DAN ALAT PENGHITUNG OTOMATIS BERBASIS ARDUINO NANO MENGGUNAKAN SENSOR INFRAMERAH PADA PRODUKSI ROTI TAWAR - Mukhlison; Sri Widoretno; Ava Muhamad Alsa Fahri Mahardika (Universitas Islam Balitar Blitar, 2024)
Bread is a staple food that is often consumed by Indonesian people and is made from wheat flour. In Indonesia, there are many small-scale bakery industries that continue to thrive despite the economic crisis. Seeing the rapid development of the bakery industry, product innovation is needed to improve business. One of them is making bread products with various variations. Not only that, bread industry entrepreneurs must know the latest trends and technology so they can adapt to current developments. Production of bread in large quantities means that bread calculations require a fast time, so producers must have tools that can increase effectiveness in production. Manufacturers need tools to count hundreds, thousands or even millions of goods. So this final project will design a conveyor belt and automatic counting device based on Arduino Nano using infrared sensors for the production of white bread. This prototype utilizes Arduino Nano and Arduino Nano components, Servo Motor, Ultrasonic Sensor, 20 x 4 LCDD, and a drive system in the form of a conveyor. It was then concluded that with this tool, the effectiveness of calculating bread production would increase, and shorten the time for producers and workers in calculating the amount of product produced.